Elimination of blinding trachoma by 2020: a call for rapid scale-up and strengthening programmes. (4th August 2014) - Haddad, Danny; Gebre, Teshome; Rono, Hillary
Abstract : Elimination of blinding trachoma is targeted for the year 2020, making scale-up extremely urgent. Preferred practices have been developed for mass drug administration and trichiasis surgery to assist new countries and districts. However, these need to be utilised on a broader scale to ensure quality output of programmes and the highest coverage possible of their implementation. Although in recent years there has been a significant increase in programmatic funding, there are still gaps. In addition, continued insecurity in several regions and outbreaks that require refocusing of staff threaten the goal. Close partnerships and collaboration enable the trachoma community to be well on track to reaching the goal, but it cannot be business as usual to achieve this.